Polyploidy Index and Its Implications for the Evolution of Polyploids - Wang, Jinpeng; Qin, Jun; Sun, Pengchuan; Ma, Xuelian; Yu, Jigao; Li, Yuxian; Sun, Sangrong; Lei, Tianyu; Meng, Fanbo; Wei, Chendan; Li, Xinyu; Guo, He; et al. (Frontiers in Genetics, 2019)
Polyploidy has contributed to the divergence and domestication of plants; however, estimation of the relative roles that different types of polyploidy have played during evolution has been difficult. Unbalanced and balanced gene removal was previously related to allopolyploidies and autopolyploidies, respectively. Here, to infer the types of polyploidies and evaluate their evolutionary effects, we devised a statistic, the Polyploidy-index or P-index, to characterize the degree of divergence between subgenomes of a polyploidy, to find whether there has been a balanced or unbalanced gene removal from the homoeologous regions. Based on a P-index threshold of 0.3 that distinguishes between known or previously inferred allo- or auto-polyploidies, we found that 87.5% of 24 angiosperm paleo-polyploidies were likely produced by allopolyploidizations, responsible for establishment of major tribes such as Poaceae and Fabaceae, and large groups such as monocots and eudicots. These findings suggest that >99.7% of plant genomes likely derived directly from allopolyploidies, with autopolyploidies responsible for the establishment of only a few small genera, including Glycine, Malus, and Populus, each containing tens of species. Overall, these findings show that polyploids with high divergence between subgenomes (presumably allopolyploids) established the major plant groups, possibly through secondary contact between previously isolated populations and hybrid vigor associated with their re-joining.